Juvenile Myoclonic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The clinical and EEG features and reasons for frequent misdiagnosis of juvenile myoclonic epilepsy are reviewed by the Epilepsy Research Group, Institute of Neurology, National Hospital, and St Thomas' Hospital, London, England.